Analysis of Successful Cases of Sustainable Economic Development through Project Management in the Post-War Reconstruction of Ukraine - Holovnia, Yuliia; Zhurba, Oleksandr; Zakharchuk, Volodymyr; Verbovska, Lesya; Havran, Volodymyr (International Journal of Economics and Financial Issues, 2025)
After wars, nations have problems reconstructing their nation, Ukraine. Unfortunately, the Middle has been struck by profound infrastructure destruction, economic disruption and fragmentation of society that continues in conflict. This study investigates how project management contributes to sustainable economic development in Ukraine’s reconstruction in 2023 through some projects being pursued. The study used a mixed method approach, qualitative case studies and quantitative analysis, which included the unit root test of ADF, Johansen cointegration test and ARDL long run and short run estimates to assess the impact of project management variables. The study finds that short- and long-term sustainability outcomes are driven by Community Impact, Stakeholder Engagement, and International Support. The ECT value showed rapid adjustment to equilibrium, and results from the ARDL long run showed that these variables had substantial effects. The main policy recommendation is to improve collaboration and promote innovation whilst emphasising resource efficiency. This research provides a complete framework for integrating project management with sustainable development in post-conflict reconstruction and actionable insights for Ukraine’s recovery.